Reconstruction of the Medial Patellofemoral Ligament Through a Double Bundle of a Single Patellar Tract and Quadriceps Tendon: A Modified Technique - Shengrui Wang, M.M.; Guorui Cao, M.D.; Xiao Wang, M.M.; Xiaotao Shi, M.M.; Lanbo Yang, M.D.; Jinyang Yu, M.M.; Honglue Tan, M.D. (Arthroscopy Techniques)
The medial patellofemoral ligament (MPFL) is one of the important structures that maintains patellar stability during knee flexion and extension. For patients with patellar dislocation, timely surgical reconstruction of the MPFL can reduce the risk of patellofemoral joint degeneration. Different methods of MPFL reconstruction have been reported in the literature. However, complications such as patellar fracture, postoperative foreign body stimulation, and fixation failure caused by inappropriate graft tension are common clinical problems. Therefore, on the basis of physiological anatomy, we present our surgical technique for MPFL reconstruction. The advantages are that the single bone tunnel is easy to use, effectively simulating the physiological anatomy of the medial support structure of the knee joint; a good fixation effect is achieved; and costs are decreased.